ANALYSIS OF COST STRUCTURE, REVENUE, AND PROFITABILITY OF TOFU PRODUCTION BUSINESS (CASE IN WAHYU UTAMA UKM, GUNUNG PUTRI, BOGOR REGENCY) - Siti Rochaeni; Rizky Adi Puspita Sari; Desita Prastiwi (AGRIBUSINESS JOURNAL, 2022)
Tofu  is one of the popular    processed soybean  products  for  the people  of     Indonesia. Wahyu Utama UKM is one of   the       medium-scale   tofu   processing  industries in Bogor Regency , with  tofu  products sold  are  white tofu   consisting of  small        tofu  products  and      big tofu products. Wahyu Utama UKM, which  has   been operating  since    2018, unfortunately does not   have a  systematic  cost recording, does not   know  the   income that has been  obtained,  has  not  done  calculations  The efficiency of   its business, and also faced  with the   sales of  tofu  products  in TahuN  2021 which tends to  decline.  The objectives of   this  study  are  (1) Analyzing  the cost structure of    Wahyu Utama SMEs in  producing  tofu; (2) Analyzing  the  income of  tofu  production  business in Wahyu Utama SMEs; (3) Analyzing  the level of  B/C Ratio, Break Even Point (BEP), and  Payback Period (PP)  in   tofu  production businesses  in Wahyu Utama SMEs; (4) Analyze the   profitability of  tofu  production  business  in Wahyu Utama SMEs.  The research  was conducted  at Wahyu Utama UKM,  Bogor Regency .  Types of  quantitative  research  with  descriptive  analysis.  The data source uses  primary data and secondary  data.    The data  analysis used  is  descriptive analysis to   find out the   general  description of   the company, business   cost  structure,   business revenue   analysis  to  measure  revenue     , and revenue, followed by   business analysis with   B/C Ratio, Break Even Point (BEP), and Payback Period (PP),  as well as   business  profitability    analysis    with  Margin of Safety (MOS) and Marginal Income Ratio (MIR).    The results   showed   that  (1)  The   variable   costs needed   by   Wahyu Utama SMEs have  a   higher  percentage  compared to   fixed  costs, as for the   largest  cost component    to  produce    small tofu products and   big      tofu products are the cost   of purchasing  soybeans, while the   smallest    cost component    isthe  cost of  land  and building  taxes; (2)   The business revenue of tofu products in   Wahyu Utama SMEs in  2021 was IDR   1,234,274,167 which came  from the   income of   small tofu products of IDR   675,788,202 and   large      tofu    products    of    IDR 558,485,965; (3) The value   of the B/C Ratio in small tofu products   is 0.19 and in   large tofu products   which is  0.15,  the result  of  the B/C Ratio   value obtained  in    small tofu products     and   big        tofu  products  has been   reaching a   number  of more  than  zero, so it  can be  said that  the tahu  production  business  in Wahyu Utama SMEs is profitable  or  provides  benefits; sales volume   and product receipts     know that Wahyu Utama SMEs are  already greater than   the   calculation  of the   Break Even Point (BEP)   value, so it  can  be said that the   tofu  production  business  in Wahyu Utama SMEs is profitable;      the Payback  Period (PP)  value   of Wahyu Utama   SME   tofu production  business is   0.76, which means that  Wahyu Utama SMEs experience  a return of   capital within  9 months  and 4 days; (4) The profitability obtained  from the     small   tofu   product business   is   16.38 percent, and   the   big  tofu product    is    13.08 percent.  This   shows that  the Wahyu Utama SME     tofu product   business has  good   prospects  to  be cultivated  and developed  because it   generates  profits.